Penyuluhan dan Pelatihan Pengelolaan Sosial Media kepada Karang Taruna Cerdas, Sapen, Sukoharjo - Jaka Suyana; Komariah Komariah; Sumani Sumani; Dwi Priyo Ariyanto; Jelita Widya Kusuma; Silvia Novarinda (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2025)
Youth associations (Karang Taruna) are a very important organization in the development of the surrounding village area. The existence of youth associations are very important to support and develop. One of the important efforts made is by introducing and teaching social media management, now with social media you will get various information and benefits. With the outreach and training on several social media, it is hoped that it will be able to restore the enthusiasm and awareness of the Cerdas youth association to continue its activities, and it is hoped that it will be able to increase the skills of the youth association members so that they can provide benefits for both the organization, society and themselves. Apart from that, this devotion also aims to find out the hopes of the Cerdas youth association in the future after counseling and training. The method of service activities is carried out using a qualitative descriptive approach, namely through observation, interviews, documentation, and implementation of service programs. The results of the training showed that Cerdas youth association's ability reached more than 95% in the aspects of basic understanding, practice, mastery, and use of social media. The conclusion is that providing counseling and training on several software and applications related to social media, this is able to restore the enthusiasm and awareness of Cerdas youth association to continue its activities, and is able to increase the skills of Youth Organization members so that they can provide benefits for both the organization, society and themselves.